An Application of Alternative Method of Transformation - Wan Muhamad Amir Bin W Ahmad; Nyi Nyi Naing; Mohd Tengku Ariff Raja Hussein (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2007)
Data transformation plays a major role when behave of the data do not meet the assumption of linearregression and ANOVA. In this paper we will demonstrate an application of the alternative method oftransformation, so that the assumptions of ANOVA are met (or violated to a lesser degree). These datawere collected from biostatistics experiments. Some of calculation is done by manually and the restby the MINITAB software. The results will be discussed at the end of the paper.